Effect of Compost Fertilizer and NPK Rainbow Compound Fertilizer on Growth and Yield of Beans (Phaseolus vulgaris L). - Ipentiana, Nani; Syahfari, Helda (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2018)
The study aimed to determine the effect of compost and NPK Pelangi compound fertilizer and their interaction on the growth and yield of beans.The study was conducted in February-May 2016. The location of the study was in Linggang Amer Village, Linggang Bigung District, West Kutai Regency. The research design used was a Completely Randomized Design (CRD) in a 4x4 factorial experiment with 3 replications. Factor I: dosage of compost (B), consists of 4 levels, namely: without fertilizer or control (b0), fertilizer dose of 10 tons / ha or 100 g / polybag (b1), fertilizer dose of 20 tons / ha or 200 g / polybag (b2), fertilizer dose of 30 tons / ha or 300 g / polybag (b3). The second factor: the dose of NPK Pelangi (P) compound fertilizer, consists of 4 levels, namely: without fertilizer or control (p0), 1 g / polybag (p1) fertilizer dose, 3 g / polybag (p2) fertilizer dose, 5 fertilizer dose g / polybag (p3).The results showed that compost treatment (B) had no significant effect on the height of plants aged 10 and 30 days after planting, the number of fruit per plant and the weight of fruit per plant. The effect is very significant on plant height aged 20 days after planting and fruit length. The treatment of NPK Pelangi compound fertilizer (P) had no significant effect on plant height aged 20 and 30 days after planting, fruit length, number of fruit per plant and weight of fruit per plant. Significant effect on plant height at 10 days after planting.